Beam interference suppression in multi-cell millimeter wave communications - Zufan Zhang; Honghui Yu (Digital Communications and Networks, 2019)
Due to the increase in the number of users, beam switching is used for suppressing interference, which leads to higher computational complexity in multi-cell millimeter wave communications. In order to resolve this problem, a beam interference model is introduced, and a lower complexity beam interference suppression algorithm based on user grouping is proposed. The proposed algorithm operates beam switching and multi-cell cooperative transmission for a part of the users when there exists beam interference due to high user density. In particular, considering the distinct interference suffered by each user, the proposed dual-threshold user grouping method can effectively solve the frequent switching problem at the base station caused by multi-cell cooperative transmission in multi-cell environments. Simulation results show that the proposed algorithm can reduce the computational complexity of beam switching and approach ideal system capacity, compared with conventional interference suppression algorithms that do not involve grouping of users. Keywords: Millimeter wave, Beam interference, Beam switching, User grouping, Multi-cell cooperative transmission